Role of Homoeopathy in Sports Medicine – A Review (Homoeopathy for All, 2022)
Sports injury is the general term being used for the documentation of health problems caused by participation in sports and physical exercise. According to Engebretsen et al. a sports injury may be defined as “damage to the tissues of the body that occurs as a result of sport or exercise”.1Participation in sports is one of the major activity for the promotion of physical health. However, injury is an important adverse effect of the sports. It is the significant barrier to carry on physical activity. As per the report, physical activity is accountable for 6 to 10 % of no communicable diseases in 2008 and 5.3 million deaths are recorded due to it.2Muscle strain injury, muscle contusion injury, muscle cramps, muscle laceration and chronic tensile overload injuries are the common injuries that occur due to sports.3As per the report males are recorded more injuries than females. In the sports injury running was reported most contributing sports followed by football, handball and gymnastic.4 Epidemiological study shows that lower limb injuries are most common in basketball (63.7%) with 21.9% ankle injuries and 17.8% knee injuries regardless of gender and category.5 Injuries like torn anterior cruciate ligament (ACL), concussion, hamstring injury, fracture and patellar tendon tear can prevent athlete to enjoy physical activity throughout the life.6Sports injuries sometime can be slow and frustrating. Physiotherapy is considered as the conventional mode of treatment for the recovery from the sports injury along with harmful painkillers. It has been reported clinically that such injuries are not been completely healed by such measures. In cases of anterior cruciate ligament tear, conventional doctors advise for the surgery. Homeopathic medicines can be beneficial to speed up the recovery. In this article, we will briefly go through the literatures on efficacy of homoeopathy in sports injuries along with its therapeutic indication.
Keywords: Medicine; Sports; injury